State of the Art in Degenerative Cervical Myelopathy: An Update on Current Clinical Evidence. Issue 3 (21st February 2017) - Wilson, Jefferson R.; Tetreault, Lindsay A.; Kim, Jun; Shamji, Mohammed F.; Harrop, James S.; Mroz, Thomas; Cho, Samuel; Fehlings, Michael G.
Abstract: Degenerative cervical myelopathy (DCM) is a common cause of spinal cord dysfunction that confronts clinicians on a daily basis. Research performed over the past few decades has provided improved insight into the diagnosis, evaluation, and treatment of this disorder. We aim to provide clinicians with an update regarding the state of the art in DCM, focusing on more recent research pertaining to pathophysiology, natural history, treatment, consideration of the minimally symptomatic patient, surgical outcome prediction, and outcome measurement. Current concepts of pathophysiology focus on the combination of static and dynamic elements leading to breakdown of the blood–spinal cord barrier at the site of compression resulting in local inflammation, cellular dysfunction, and apoptosis. With respect to treatment, although there is a dearth of high-quality studies comparing surgical to nonoperative treatment, several large prospective studies have recently associated surgical management with clinically and statistically significant improvement in functional, disability, and quality of life outcome at long-term follow-up. When selecting the specific surgical intervention for a patient with DCM, anterior (discectomy, corpectomy, hybrid discectomy/corpectomy), posterior (laminectomy and fusion, laminoplasty), and combined approaches may be considered as options depending on the specifics of the patient in question; evidence supporting each of these approaches is reviewed in detail. Recently developed clinical prediction models allow for accurate forecasting of postoperative outcomes, permitting enhanced communication and management of patient expectations in the preoperative setting. Finally, an overview of outcome measures recommended for use in the assessment of DCM patients is provided.